PERAN NOTARIS DAN KETERANGAN AHLI WARIS DALAM PENYELESAIAN SENGKETA KEWARISAN - Muhammad Nur Fikri; Si Ngurah Ardhya; Ratna Artha Windari (Jurnal Pacta Sunt Servanda, 2024)
Inheritance disputes frequently arise due to uncertainty regarding heirs and inherited assets, necessitating legal instruments that ensure legal certainty and protection for the parties involved. In this context, notaries and certificates of heirs play a strategic role in evidentiary processes and the resolution of inheritance disputes. This study aims to analyze the role and authority of notaries in drafting inheritance-related deeds and to examine the legal standing of certificates of heirs as evidence in inheritance disputes. The research employs a normative juridical method using statutory and conceptual approaches, supported by a literature review of primary and secondary legal materials. The findings indicate that notaries hold a central authority in producing authentic deeds, such as wills and deeds of heirs’ statements, which possess strong evidentiary value and serve a preventive function in minimizing disputes. Meanwhile, certificates of heirs constitute an important form of written evidence; however, their evidentiary strength is relative and depends on their form, issuing authority, and consistency with other evidence. Therefore, the resolution of inheritance disputes requires an integrated approach involving notarial authority and judicial discretion in evaluating evidence comprehensively.